Measuring patient experience in a safety net setting: Lessons learned - Nina Shabbat; Katy Dobbins; Sonja Seglin; Kristin Davis (The Beryl Institute, 2015)
Safety net providers have faced barriers in administering patient experience surveys due to a lack of resources and survey expertise, but this problem has received little attention in the literature. In this manuscript, we offer lessons learned from the administration of a patient experience survey at a mid-size behavioral health care agency serving a safety net population. Specifically, we discuss resource needs, methods of increasing response rate among transient populations, methods for engaging stakeholders and clinical staff in quality improvement initiatives, and considerations for responding to setbacks and challenges dynamically. We also offer insight on the effective dissemination of results within safety net organizations and discuss the role of organizational culture.